14 Years after Discovery: Clinical Follow-up on 15 Patients with Inducible Co-Stimulator Deficiency - Schepp, Johanna; Chou, Janet; Skrabl-Baumgartner, Andrea; Arkwright, Peter D.; Engelhardt, Karin R.; Hambleton, Sophie; Morio, Tomohiro; Röther, Ekkehard; Warnatz, Klaus; Geha, Raif; Grimbacher, Bodo (Frontiers in Immunology, 2017)
Background: ICOS deficiency was the first monogenic defect reported to cause common variable immunodeficiency (CVID)-like disease in 2003. Since then 16 patients have been reported worldwide with an increasing range of clinical phenotypes. Objective: We sought to compare the clinical and immunological phenotype, and provide clinical follow-up and therapeutic approaches for treating ICOS-deficient patients. Methods: We describe the clinical and laboratory data of 15 patients with available clinical data. Previous publications and clinical assessment were used as data sources. Results: The observed ICOS gene mutations were all deletions leading to undetectable protein expression. The clinical phenotype of ICOS deficiency is much broader than initially anticipated and includes not only CVID-like disease but an increased susceptibility to viral and opportunistic infections, as well as cancer. Impaired B-cell development led to decreased memory B-cells in all patients, and hypogammaglobulinemia in all but one patient. Circulating CXCR5+ CD4+ follicular T-helper-cell numbers were also reduced in all patients. Treatment included immunoglobulin replacement, regular antibiotic prophylaxis, corticosteroids and steroid-sparing agents. Three patients underwent hematopoietic stem cell transplantation; one of them died due to capillary leak syndrome on day five post-transplantation. Conclusion: The disease spectrum of ICOS deficiency is expanding from solely B-cell to combined B- and T-cell immunodeficiency, suggesting genetic and environmental modifiers. Genetic diagnosis is the only tool to distinguish ICOS deficiency from other immunological defects. Patients with antibody deficiency, autoimmunity, and combined immunodeficiency should be screened for ICOS mutations.